DIGITAL DETOXIFICATION: EVALUATING INTERVENTION STRATEGIES FOR ADOLESCENTS - Soumya Sonalika; Jacqueline D. M. Williams; Sikandar Kumar (Journal of Mechanics of Continua and Mathematical Sciences)
Excessive digital use among adolescents is increasingly linked to adverse mental health, reduced productivity, and impaired academic performance. Digital detoxification, a strategy involving temporary disengagement from digital devices, has emerged as a promising intervention. This study evaluates the efficacy of an interventional package designed to promote digital detoxification among adolescents in Bhubaneswar, Odisha. Using a pre-experimental, randomized control group design, 500 students were enrolled and divided into intervention and control groups. Significant reductions in digital use were observed in the intervention group postintervention (mean difference = 39.5, p< 0.05), while no notable changes were recorded in the control group. The intervention group showed a significant reduction in digital use following the intervention, with the post-test mean score decreasing to 36.2 (SD = 28.46), indicating the effectiveness of the intervention (p < 0.05). In contrast, the control group exhibited no significant change in digital use, as the posttest mean remained at 75.6 (SD = 46.67), suggesting that without intervention, digital use levels remained stable (p > 0.05). The findings underscore the potential of structured interventions to foster healthier digital habits, with broader implications for educational policies and adolescent health.